Core strength training of female discus throwers - Lin, D. H.; Xie, Z. W. (Shandong Sports Science and Technology, 2011)
By using the methods of documentation, and combining with my years of practices in women's discus training as well as researches on core strength training method,I figure out that the selection of core strength training methods and means is highly related with special scores.Therefore,in order to fully bring out athletes' potential,we can aim at developing the fast power of muscle chain in core parts.Based on the feature of the original phosphoric acid system,we reasonably arrange exercises and intermittent time,and reasonably arrange the order of strength training means.Futhermore,perfectly and more effectly to combine the core strength and technology rhythm.